IMPROVING PULMONARY TUBERCULOSIS SURVEILLANCE THROUGH EDUCATION: IMPACTS ON THE COMPETENCE OF HEALTH WORKERS AND CADRES - Age, Sulastri Pua; Faisal, Faisal; Mustafa, Yanti (International Journal of Health Science & Medical Research, 2026)
Optimizing the understanding of the pulmonary tuberculosis (TB) epidemiological surveillance system among health workers and health cadres is crucial for effective TB prevention and control. Unlike previous studies that mainly focus on clinical aspects of TB management, this study introduces a structured educational workshop that emphasizes epidemiological surveillance competencies and simultaneously involves health workers and community health cadres at the primary healthcare level, representing a collaborative capacity-building approach in TB control. This study aimed to analyze the impact of educational interventions in improving knowledge and skills related to pulmonary TB surveillance. A quasi-experimental design with one group pre-test and post-test was employed. The intervention involved an educational workshop on strategies for implementing the TB surveillance system. Thirty-two participants (8 health workers and 24 health cadres) were selected using purposive sampling, as they were actively involved in TB prevention and control at community health centers (Puskesmas). The Paired Sample T-test results showed a significant increase in knowledge after the intervention (p = 0.004), with a strong correlation between workshop participation and improved understanding (r = 0.857; p 0.001). These findings indicate that structured educational workshops significantly enhance participants’ comprehension of the TB epidemiological surveillance system. Continuous education and periodic training at Puskesmas are therefore essential to strengthen the role of health workers and cadres in monitoring, preventing, and controlling pulmonary TB transmission.